Structure-activity relationships studies in drug development by NMR spectroscopy (Royal Society of Chemistry, 2011)
The book comprises seven scholarly written articles on this multifaceted technique. Mailavaram and Devarakonda skillfully summarize the broad approaches of NMR-based drug discovery in their introductory review. Park and Kim in their review focus on the use of NMR ectroscopic techniques in the study of drug delivery, release and other pharmaceutic parameters. Roberto and Marina provide a chronological account of fragment-based drug discovery by using NMR-based screening methods. Specific utilization of NMR-based techniques in the discovery and development of anticancer drugs is reviewed by Solomon and Lee.